PENGARUH RETURN ON EQUITY DAN DEBT TO EQUITY RATIO TERHADAP PRICE TO BOOK VALUE PADA PT INDOFOOD CBP SUKSES MAKMUR TBK PERIODE 2014-2023 - Sidiq Nurzaman; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Return on Equity and Debt to Equity Ratio on Price to Book Value at PT Indofood CBP Sukses Makmur Tbk. The method used is a quantitative approach with descriptive and verificative analysis, utilizing secondary data from the company's financial statements for the period 2014-2023. Data analysis includes descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination, as well as hypothesis testing (t-test and F-test), conducted with SPSS version 27 at a 5% significance level. The results show that partially, ROE does not have a significant effect on PBV, with t-count 1.096 < t-table 2.365 and a significance value of 0.310 (> 0.05). DER has a negative and significant effect on PBV, with t-count -3.714 < -t-table -2.365 and a significance value of 0.008 (< 0.05). Simultaneously, ROE and DER significantly affect PBV, with an F-count of 38.291 > F-table 4.737 and a significance value of 0.001 (< 0.05). The Adjusted R Square value of 89.2% indicates that most of the variation in PBV can be explained by ROE and DER, while the remaining 10.8% is influenced by factors outside the scope of this study.